Literature Review Article: Drug Delivery System Held in the Stomach (Gastroretentive) - Nurhalifah Nurhalifah; Prayoga Daffa Sundawan; Santika Citra Veronita; Shella Imka Puji Destria; Siti Nuryamah; Nia Yuniarsih (International Journal Labs, 2022)
Background: Medicine is a substance that through its chemical effects brings about changes in biological functions. The GRDDS delivery system is a sustained drug delivery system that can hold drugs back in the stomach for a longer time. The advantages of GRDDS include being able to increase bioavailability, increase the solubility of drugs that are poorly soluble in high pH, can control of therapeutic levels to reduce the occurrence of fluctuations, can extend the half-life so that the frequency of drug administration can be reduced. Objectives: This study aims to describe the types of GRDDS preparations. The variation is due to a combination of differences in mechanisms and technology. Method: The design in this study uses a systematic review of the review process that identifies, assesses, and interprets all findings on a research topic. Result: Floating systems can use expandable polymeric materials such as HPMC and chitosan. The floating mechanism begins with the contact of gastric juices with tablets which causes the polymer to hydrate to form a gel layer that can withstand CO2 gas formed due to the interaction of sodium bicarbonate with citric acid so that the tablets can expand and can float. The oral drug delivery route is the most preferred because it is easy to use. Absorption of oral drugs mostly occurs in the stomach and the intestines. Conclusion: Therefore, it is necessary to have a drug delivery system that can extend the contact time with the stomach, namely the Gastroretentive Drug Delivery System (GRDDS).